Mural Removals During COVID-19 Pandemic: Violation of Freedom of Expression? Penghapusan Mural Selama Pandemi COVID-19: Pelanggaran Kebebasan Berekspresi? - Aulia Paramita; Rifqi Ridlo Phalevy (Universitas Muhammadiyah Sidoarjo, 2023)
This COVID-19 pandemic has caused a decline in the community's economy, leading the government to issue policies that are deemed unsatisfactory by the people. As a result, it has spurred artists to create murals containing criticism of the government. However, the public perceives the government to be against criticism because they have removed murals, which is deemed to have violated local regulations and forgotten that everyone has the right to freedom of expression. This study aims to analyze the implementation of the Pasuruan City Regional Regulation No. 2 of 2017 Article 19 Letter a and assess the compatibility of the regulation with Law No. 39 of 1999 concerning Human Rights. The research method used is socio-legal method, and the results of this study indicate that the removal of murals was not based on human rights. Therefore, this study concludes that there should be a special treatment for murals with critical content. Highlights : COVID-19 pandemic has led to a decline in the community's economy, which has resulted in the government issuing unsatisfactory policies. Murals have been created by artists to criticize the government, but the removal of these murals by the government has sparked public outrage. The study found that the removal of murals violated human rights, and therefore, there should be a special treatment for murals with critical content. Keywords: Mural removals, COVID-19 pandemic, Freedom of expression, Government policies, Human rights.